Jewish life in the Middle Ages - Abrahams, Israel, 1858-1925 (Kegan Paul library of archaeology and history., 2005)
""Jewish Life in the Middle Ages"" is a fascinating and well-known look at life in the middle ages for the Jewish community. The author also gives attention to how the European movements of the middle ages were affected by Jewish influences. Topics addressed include: social functions of the synagogue, decay of the sermon in the middle ages, the origin of the word ""ghetto,"" family feasts and fasts, and the ethics of dress.